Optimizing two phase thermophilic anaerobic digestion utilizing food waste for production of biogas - Menon, Ajay Shivadasan (2018)
Anaerobic Digestion (AD) is a method of treating organic wastes where microbial activity is used to remove biodegradable solids while producing energy rich products like hydrogen and methane. Thermophilic AD has been shown to have higher productivity than conventional mesophilic AD, however it has issues such as lower stability and is not as well studied. In this thesis, thermophilic AD of food waste was optimised by dividing it into two phases- acidogenic and methanogenic- and optimising each phase separately. The acidogenic phase was optimised by developing a pretreatment method which combined alkaline and ultrasonic pretreatment. This greatly improved hydrogen production by enriching Thermoanaerobacterium thermosaccharolyticum in the acidogen community. The methanogenic phase was optimised using a novel micronutrient supplement containing optimal concentrations of calcium, magnesium, cobalt and nickel, which both stabilised and increased methane production by increasing the bacterial diversity and hence improving the functional diversity and redundancy of the methanogenic community.